The Effect of Nursing Range of Motion on the Motor Function of Patients with Impaired Physical Mobility - Lilis Setyowati; Elma; Erma Wahyu Mashfufa; Ollyvia Freeska Dwi Marta; Nur Aini (Formosa Journal of Science and Technology, 2023)
CVA occurs when there is a disturbance in blood circulation in the brain. Hemiparalysis is complicated by CVA, which causes impaired physical mobility. ROM exercises can maintain and improve joint mobility. This study aims to analyze the effectiveness of ROM intervention in patients with impaired physical mobility CVA Infarc. The case study research design. Participants in the first attack, CVA, were admitted to a government hospital in Malang. ROM implementation was given for four days and carried out 2x/a day for 15 minutes. After doing ROM exercises the patient's initial muscle strength score was 2 to 3. Patients were independent in fulfilling ADL. ROM exercises given immediately while in the hospital can increase muscle strength. Besides that, supporting families, dan emotional patients help maximize the result.